Effectiveness of Loans or Financing and Portfolio Management with Problems or Non-Performing Loans The Impact on Asset Growth in Islamic Banks in Indonesia - Agus Supriatna; Faisal Faisal (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
The study was conducted to see whether there was a significant impact of credit or financing and portfolio management of problem loans or non-performing loans on asset growth in Islamic banks in Indonesia in 2009-2018, either partially or simultaneously. This type of research is descriptive quantitative using secondary data types obtained from the published financial reports of three major banks in Indonesia, namely Bank Muamalat Indonesia or BMI, Bank Rakyat Indonesia Syariah or BRI Syariah and Bank Syariah Mandiri or BSM from the Bank's third Annual Report, from 2009 until 2018. The data analysis method uses classical assumption test techniques and Linear Regression Analysis techniques, Correlation Coefficient test, partial Hypothesis test (t test), simultaneous test (F test) and Determination Coefficient test with Credit or Financing Effectiveness variables (X1 ) and Portfolio Management of Non Performing Loans is a variable (X2) and Asset Growth the Islamic Banks in Indonesia as a variable (Y). Tests conducted using the Eviews application version 10. Then the results of the study with the multiple regression equation PA = 37.424.6 + 1.364393 EK_P + 3.289641 NPL with the value of Fcount (595.2748)> from Ftable (2,3003) significance or probability (α) 0.000 <0.05. Simultaneously Effectiveness of Credit or Financing and Portfolio Management of Non Performing Loans simultaneously have an impact on Asset Growth in Islamic Banks in Indonesia. The Adjusted R-Square (R2) value of 0.976182 shows that the contribution of the EK_P and NPL variables to the PA variable is 97.6182% while 2.3818% is seen by other factors.